MORAL ISSIUES AND MOTIVE OF LONELINESS IN KITE RUNNER AND A THOUSAND SPLENDID SUNS BY KHALID HOSSEIN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This study is an analysis of the aims of the protagonist’s struggle in Khaled Hosseini’s novel A Thousand Splendid Suns. The novel tells about a wife, the protagonist of the novel, who should live hard with a husband with bad temper. However, the protagonist by the name of Mariam keeps being a good wife for her husband. Furthermore, her husband has another wife. Unfortunately, the husband with his bad temper almost kills her. The protagonist should struggle to protect her husband’s another wife as well. The analysis is conducted by descriptive qualitative method, in which the data are analyzed descriptively.